2021
DOI: 10.1002/chem.202103178
|View full text |Cite
|
Sign up to set email alerts
|

A Series of Iron(II)‐NHC Sensitizers with Remarkable Power Conversion Efficiency in Photoelectrochemical Cells**

Abstract: A series of six new Fe(II)NHC-carboxylic sensitizers with their ancillary ligand decorated with functions of varied electronic properties have been designed with the aim to increase the metal-to-surface charge separation and light harvesting in iron-based dye-sensitized solar cells (DSSCs). ARM130 scored the highest efficiency ever reported for an iron-sensitized solar cell (1.83 %) using Mg 2 + and NBu 4 I-based electrolyte and a thick 20 μm TiO 2 anode. Computational modelling, transient absorption spectrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 34 publications
(49 reference statements)
0
24
0
Order By: Relevance
“…A recent investigation from Gros and coworkers focused on heteroleptic dyes based upon 75 ( Scheme 27 ) and bearing different substituents in the 4-position of the pyridine ring of the ancillary ligand. 281 Substituents with varying electronic properties were selected and the most efficient dye was 81 ( Scheme 27 ). DSCs were fabricated with 20 μm thick TiO 2 photoanodes, and the optimized electrolyte composition described above, i.e.…”
Section: The Holy Grail: Iron In Dscsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent investigation from Gros and coworkers focused on heteroleptic dyes based upon 75 ( Scheme 27 ) and bearing different substituents in the 4-position of the pyridine ring of the ancillary ligand. 281 Substituents with varying electronic properties were selected and the most efficient dye was 81 ( Scheme 27 ). DSCs were fabricated with 20 μm thick TiO 2 photoanodes, and the optimized electrolyte composition described above, i.e.…”
Section: The Holy Grail: Iron In Dscsmentioning
confidence: 99%
“…DSCs were fabricated with 20 μm thick TiO 2 photoanodes, and the optimized electrolyte composition described above, i.e. LiI (0.1 M), I 2 (0.1 M), PMII (0.60 M), MgI 2 (0.1 M), Bu 4 NI (0.1 M) and GNCS (0.1 M) in MeCN; the counter electrode was coated with PEDOT rather than Pt, 281 even though in a previous study, Pt was shown to be more beneficial than PEDOT. 279 The best performance was found for dye 81 which incorporates electron-donating MeO groups ( Scheme 27 and Table 10 ).…”
Section: The Holy Grail: Iron In Dscsmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Mg 2+ cations are capable to adsorb at the sensitizer/semiconductor interface and to improve the interfacial electron transfer kinetics (regeneration and/or electron injection), thus resulting in higher measured photocurrents. 33 This result was very recently further improved by our group up to reach the best efficiencies ever reported of 1.44 % (Jsc = 4.8 mA/cm 2 ) and 1.83% (Jsc = 4.8 mA/cm 2 ) by sensitizing FeSSCs respectively, with the heteroleptic complexes ARM13 33 and ARM130 34 (Figure 1). The heteroleptic approach was also recently applied by Warnmark that reported the introduction of diarylamino substituents on the central pyridine of the ancillary ligand resulting in 1.31% efficiency and Jsc = 3.5 mA/cm 2 .…”
Section: Introductionmentioning
confidence: 62%
“…The MLCT lifetime has reached tens of picoseconds for complexes with tridentate C^N^C [18][19][20] and bidentate C^N ligands, [21][22][23][24] and nanoseconds for compounds bearing tridentate C^C^C ligands, 25 making it possible for iron to be used in photochemical applications such as iron-sensitized DSSCs. [26][27][28][29][30][31] However, apart from the recently published Fe(II) complex with phenN,N′^C ligands, 32 this improvement in lifetime was obtained at the sacrifice of achieving the panchromatic absorption required for solar energy conversion applications. Recently, "HOMO inversion" has emerged as a promising concept in the field.…”
Section: Introductionmentioning
confidence: 99%